Legal Pluralism and the Threat to Human Rights in the New Plurinational State of Bolivia - James M. Cooper (Washington University Global Studies Law Review, 2018)
Bolivia, the chronically poor, landlocked Andean country has long seen its indigenous populations marginalized, languishing in underdevelopment. Spanish colonialists destroyed any vestige of the vibrant, complex civilization that existed in the region – including the religious, political and legal systems in place for centuries. In December 2005, Evo Morales Ayma was the first elected President of indigenous descent. After leading the changes in the country’s Constitution, Morales continued to rule Bolivia until the writing of this Article. The New Political Constitution of Plurinational State of Bolivia of 2009 and a national law for community justice, signed into law by Morales, provided the foundations for a legally pluralistic judicial system – one in which traditional customary law works in parallel with a more Western-styled system. While the right of self- determination and indigenous autonomy are promoted with this bifurcated system of justice, there are many challenges to the international human rights standards to which Bolivia has acceded as part of its participation in the United Nations and Inter-American international legal systems. This Article lays out the many treaty regimes of which Bolivia is a member and the ways in which Bolivian customary law allowing for indigenous traditions violates Bolivia’s international legal obligations. The final part of the Article provides a brief survey of legal pluralistic projects in other countries around the world and the ongoing struggle in balancing the right of self-determination for Indigenous Peoples with international human rights standards and protections.
Keywords: Human rights; pluralism; Bolivia; Constitution; indigenous; protection